氷板混合津波が橋桁に及ぼす波力特性に関する実験的研究 - 佐藤, 好茂; 阿部, 孝章; 吉川, 泰弘; 伊藤, 丹 (Journal of Japan Society of Civil Engineers, Ser. B2 (Coastal Engineering), 2014)
In the event of a winter tsunami, there is the concern that floating ice sheets originating from sea ice might impact structures if the ice is carried by tsunami run-up. Accordingly, we conducted hydraulic model tests that reproduced the vertical and longitudinal behaviors of floating ice sheets carried by tsunami run-up. We clarified the characteristics of wave force for tsunamis that contain sea ice sheets and the impact of such tsunamis against bridge girders. In this test we reproduced a flow that contained solid substances and liquid substances. We confirmed that the wave force of a tsunami whose ice cover rate is 80% is about 2.5 times the wave force of a tsunami that contains no ice. We succeeded in showing the wave force characteristics of tsunami waves containing water and ice running up rivers in winter for bridge girder structures. journal article